(3EOGQI GdeHjYGJ hGdHjY GdTNUjs - (3eMeO(B, (3YHjOGJs ((3YeGf(B:s (3OGQ hGFd ddWHGYI h GdfTQ(B,s, 2001)
(3ebOeI aj EOGQI GdeHjYGJ , EOGQI Gdbhi GdHjYjI, JNWjW GdeHjYGJ, Jbjje COGA GdfTGW GdHjYjs
(3GdeQGLY U(B.317s
Keywords: (3GdHjYs; (3GdJShjbs